A novel approach to obtain conductive tracks on PP/MWCNT nanocomposites by laser printing. Issue 34 (18th March 2016) - Colucci, G.; Beltrame, C.; Giorcelli, M.; Veca, A.; Badini, C.
Abstract : Metal-free conductive tracks were obtained by laser printing on a polypropylene matrix by adding MW-CNTs. Abstract : This article aims to develop metal free conductive tracks on polymer nanocomposites based on a polypropylene matrix in the presence of MWCNTs, by using laser printing. The main purpose is to obtain electrical wiring that can replace the metal wires commonly used for electrical transmission. A complete investigation is carried out in order to study the effect of the laser processing on the polymer matrix and the influence of the MWCNTs on the electrical and thermal properties of the polymer-based nanocomposites. The paper also describes the effect of the laser on the final microstructure of the CNTs-based nanocomposites. The results obtained clearly indicate that the laser printing is a simple, flexible, and relatively low cost approach to obtain conductive tracks on PP in the presence of MWCNTs, depending on the laser parameters set up. In fact, as found, it is strictly necessary to reach a good compromise between the electrical resistance values and the final integrity of the samples, because the laser printing treatment can induce damage on the final material because of the high energy absorbed on the polymer surface and the high temperatures generated. A circuit prototype has been also designed and developed.